IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR ISLAM TERPADU AL-MADINAH KEBUMEN TAHUN 2014 - Yunus, Akhmat (Universitas Muhammadiyah Surakarta, 2015)
The emergence of the phenomenon of moral degradation in 2010 among the general public as well as in education begin much talked about character education. Many media and education experts, and community leaders recommended that character education is effective immediately. The basic reason for the character education used as the basis for forming a national development vision is to realize public morals, moral, ethical, cultural, and based on the philosophy of Pancasila. This study aims to explain the implementation of character education in the learning process in SDIT Al-Madinah Kebumen and identify constraints implementation of character education in learning, and provide solutions that done to solve the problems. This study included field research in the SDIT Al-Madinan Kebumen in 2013. The subject of research from the Principal and Elementary School Teacher in SDIT Al-Madinah Kebumen. Data collected through observation, interviews, and documentation. Data analysis performed in this study is an interactive model of data analysis techniques with encounters between data collection, data reduction, data presentation and verification of data. The research concludes that the implementation of character SDIT Al-Madinah Kebumen in the learning process has the advantage of adding the value of faith and the character-based monotheism conducted through three stages: (1) Phase formulation character which teachers formulate a list of 18 characters in SDIT Al - Madina Kebumen and distribution character, (2) Phase understanding of the character, namely schools and KKG organizes workshops that discuss the character that has been agreed on the list of characters and character distribution, (3) The planning stage of implementation of character education. Constraints Implementation of Character Education in Learning SDIT Al-Madinah Kebumen 2014 is the sequence of learning much so reducing in the implementation of character education, a lack of understanding of teachers to the formulation of the foundation of monotheism theme, the lack of cooperation between teachers and pupils, differences in parenting between home and schools, and the lack of support the behavior of people living environment of students. Solutions are formulated is the development of a maximum of two characters in each lesson, designing learning activities fun and appreciation for pupils, schools conduct coordination meetings, evaluation, and training for teachers, schools carry out the forum event class and memorandum communication relating to equalization understanding of the program, school organize parent training programs are more effective, in organizing the school community education programs, such as training stages of child development and the principle of caring.Keywords: implementation; character education; leaning.